Design and implementation of isolated multilevel inverter with lower number of circuit devices - Ahmed Abbas (290309) (2023)
Galvanic isolation is an integral part for the grid connected solar PV system. With the advancement of multilevel inverters for the grid‐connected application, the multilevel inverters having isolation are not sufficiently discussed in the literature. Here, a 15‐level isolated multilevel inverter topology requiring only 13 switches is proposed. The proposed single‐phase isolated converter requires reduced switches to generate 15‐level ac output voltage with voltage gain of 7. Comparatively, the switches connected in the proposed converter undergo less voltage stress as compared to the MLIs reported in the literature. A comparison of the proposed converter structure to the state‐of‐the art MLIs described in the literature is included. The experimental results captured on a low‐power laboratory prototype are used to validate the performance of the proposed converter. The claimed efficiency of the converter calculated using simulation results is found to be 97.1%. However, the efficiency calculated using experimental results is 95.2% at 700 W. Other Information Published in: IET Power Electronics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1049/pel2.12579